The impact of aerobic exercise in alleviating physical disorders among premenopausal women - Nur Cahyani Ari Lestari; Zulhijriani Zulhijriani; Rizky Fitri Andini; Luluk Yuliati (Institute of Computer Science (IOCS), 2025)
Premenopause is a transitional phase marked by hormonal fluctuations that often trigger physical discomfort. This study aimed to determine the effectiveness of aerobic exercise in reducing somatic symptoms among premenopausal women. A quasi-experimental pre-testÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“post-test control group design was conducted involving 58 women aged 40ÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“55 years, selected through simple random sampling. The intervention group received aerobic exercise three times per week for eight weeks, while the control group received no intervention. Physical symptoms were assessed using the somatic domain of the Menopause Rating Scale (MRS). Results showed a significantly greater reduction in somatic scores in the intervention group compared to the control group (mean difference ÃƒÂ¢Ã‹â€ Ã¢â‚¬â„¢4.6 vs. ÃƒÂ¢Ã‹â€ Ã¢â‚¬â„¢0.5; p < 0.001). Aerobic exercise demonstrated a large effect in alleviating hot flashes, joint and muscle pain, sleep disturbances, and cardiovascular-related complaints. In conclusion, aerobic exercise is an effective non-pharmacological strategy for reducing somatic symptoms during the premenopausal transition.